Problematika money politics dan efektivitas pengawasan pemilu dalam mewujudkan keadilan substantif - Himam, M. Wafiyul (Maliki Interdisciplinary Journal, 2026)
The practice of money politics has become a chronic problem that significantly weakens the legitimacy of political parties and undermines the integrity of democracy in Indonesia. This study aims to examine the effectiveness of election oversight conducted by related institutions in addressing the challenges of transactional politics in order to achieve substantive justice, using a qualitative method through a literature study approach. The findings show that election supervision still faces serious institutional obstacles, such as the erosion of independence caused by external intervention and limited operational capacity due to the minimal budget allocation, which accounts for only around 0.15% of the total state budget for election administration. In addition, the phenomenon of “constitutional oligarchy” further worsens the situation because legal mechanisms and candidate regulations are often exploited by elites through political dowries and non-transparent campaign financing. As a result, elections tend to focus merely on fulfilling formal and procedural standards while failing to realize substantive justice based on genuine popular sovereignty. As a strategic solution, this study recommends reforming political funding regulations through greater transparency, implementing real-time campaign finance audits, and strengthening a more merit-based and politically independent selection mechanism for election organizers.